Tactile stimulation reduces reactivity but does not improve the performance of Brahman’s calves - Joseph Kaled Grajales-Cedeño; Mayara Andrioli; Mateus José Rodrigues Paranhos da Costa (Acta Scientiarum. Animal Sciences, 2025)
This study aimed to evaluate the effects of tactile stimulation on the reactivity and performance of Brahman calves. One hundred and nine calves were randomly assigned to two treatments: calves that received tactile stimulation (TS, n = 57) and those that did not (NTS, n = 52). Tactile stimulation was performed for eight minutes, 12 hours after birth. The behavioral variables were collected at weaning (209.50 ± 55.83 days) by assigning reactivity scores in the squeeze chute, which ranged from one to five (one was assigned to a calm calf and five to the most reactive). A flight speed score was assigned when each calf exited the squeeze chute. Performance was assessed using the adjusted weaning weight (WW) and daily weight gain (ADG). TS female calves showed lower reactivity scores in the squeeze chute (p < 0.05) and when leaving it (p < 0.05) than  NTS calves, but no significant differences were observed in male calves between the treatments (p > 0.05). WW and GMD did not differ between the treatments (p > 0.05). In conclusion, tactile stimulation performed in Brahman’s calves at birth resulted in less reactivity in female calves without affecting their performance.